HIV Retesting of HIV-Negative Pregnant Women in the Context of Prevention of Mother-to-Child Transmission of HIV in Primary Health Centers in Rural Zambia: What Did We Learn? - Mandala, J.; Kasonde, P.; Badru, T.; Dirks, R.; Torpey, K. (Journal of the International Association of Providers of AIDS Care, 2019)
Background:: This observational study describes implementation of HIV retesting of HIV-negative women in prevention of mother-to-child transmission (PMTCT) services in Zambia. Methods:: Uptake of retesting and PMTCT services were compared across age, parity, and weeks of gestation at the time of the first HIV test, antiretrovirals regime, and HIV early diagnosis results from infants born to HIV-positive mothers. Results:: A total of 19 090 pregnant women were tested for HIV at their first antenatal visit, 16 838 tested HIV-negative and were offered retesting 3 months later: 11 339 (67.3%) were retested; of those, 55 (0.5%) were HIV positive. Uptake of the PMTCT package by women HIV positive at retest was not different but HIV-exposed infants born to women who retested HIV positive were infected at a higher rate (11.1%) compared to those born to women who tested HIV positive at their initial test (3.2%). Conclusion:: We suggest rigorously (1) measuring the proportion of MTCT attributable to women who seroconvert during pregnancy and possibly adjust PMTCT approaches and (2) addressing the substantial loss to follow-up of HIV-negative pregnant women before HIV retesting.
Keywords: Prevention of mother-to-child transmission; HIV testing and counseling; Zambia